Human Resources Management in The Country’s Border Region Faces Industry 4.0 and The Covid-19 Pandemic - Siswanto, Dwi Joko; Tegor, Tegor; Haqiqi, Fauzan; Yusmalina, Yusmalina; Susanto, Alpino (JURNAL AL-TANZIM, 2022)
This study was to see how much influence mediation of mindset changes has on human resource development and economic growth. The study used questionnaire aids, from which the questionnaire results were processed with Smart PLS 3.0 and the Sobel test, which is used to look at the indirect influence of mediation variables. Respondents involved in this study were the Karimun Regency community, with as many as 120 respondents taken using random sampling techniques. The results of hypothesis testing in this study are: first, human resource development has a significant influence on economic growth with an influence value of 14,407, more significant than the value of t value 1.96; second, human resource development has a significant value in changing mindsets of 40,679, greater than the value of t value 1.96. Third, the variable change mindset significantly influences the economic growth of 11,696 and is greater than the value of t = 1.96. Fourth, there is a significant indirect influence between human resource development and economic growth mediated by a change in the mindset of 306.25, more significant than the value of t values of 1.96.